A Survey Instrument to Assess Intake of Dietary Supplements, Related Products, and Caffeine in High-Use Populations. (3rd August 2018) - Caldwell, John A; McGraw, Susan M; Thompson, Lauren A; Lieberman, Harris R
Abstract: Substantial data on the use of dietary supplements by the general adult population are available, but many population subgroups have not been extensively studied. Because military service members and young people consume large amounts of dietary supplements, including for enhancement of physical performance, weight control, and bodybuilding, which can be dangerous, we developed a comprehensive questionnaire to characterize patterns of supplement use in these and other populations. The questionnaire has been used to study >7000 military service members and 1000 college students. This supplement article presents a detailed description of the questionnaire, which contains comprehensive questions on demographic characteristics, exercise habits, attitudes with regard to dietary supplements, and amount of money spent on supplements. Intakes of specific dietary supplements and caffeine, frequency of use, and reasons for use are assessed. The questionnaire was designed for studying dietary supplement and caffeine intake patterns with the use of paper-and-pencil administration to military populations and was modified for use with college students and for computer and Web administration. It is available online at https://go.usa.gov/xn9FP and in the Supplemental File for this publication. It can be used to study other populations if minor modifications are made. The online version of the questionnairewill be updated periodically as newversions become available. In conclusion, a validated, detailed, noncopyrighted questionnaire designed to assess the use of dietary supplements, energy drinks (and related products), and caffeine is available for use in diverse populations. The format of the questionnaire is adaptable to computer administration and scoring, and it can be customized for specific subpopulations, locations, and product categories including updates that reflect changes in the availability of supplements or availability of new products.